Analysis of Heritability and Correlation for Yield and Yield Attributing Traits in Single Cross Hybrids of Maize - Gautam, Jigyasha; Adhikari, Aakash; Ale, Pabitra; Dhungana, Babita; Adhikari, Anup; Dhakal, Krishna Hari (International Journal of Environment, Agriculture and Biotechnology, 2022)
It is very important to study and understand the inter-relationships among the yield and yield attributing traits as well as heritability for the increased efficiency of the breeding programs. Thus, this research is meant to examine economic and biological performance and then measure the correlation between these traits and their heritability. A field experiment was performed in a Randomized Block layout with three replications, every assigned with fifteen treatments in Bharatpur, Chitwan. Effects confirmed considerable variants among all the found quantitative data. Days to tassel initiation were positively and significantly correlated with days to silking (0.83***), days to maturity (0.85**), and days to anthesis (0.87**). Thousand seed weight was significantly and positively correlated with shelling percentage (0.34*). Grain yield was significantly and positively correlated with cob length (0.32*) and number of grains per row (0.33*) whereas highly significant and positively correlated with circumference (0.43***). Traits like days to maturity (0.3), shelling percentage (0.3), and grain yield (0.6) exhibited moderate heritability while others exhibited low heritability. RL-294/CML-226 had the highest grain yield (7.7 t/ha) and grain per row (15.2) with medium performance for other characters. RML-57/RL-174 recorded the highest rows per cob (39.7), cob length (18cm), and shelling percentage (80%) whereas the lowest days to maturity (116.7 DAS) and fluctuating performance in others. Variety RML-86/RML-146 showed better consistent performance for all the traits with the third-highest grain yield (7.1 t/ha) except for shelling percentage (which was the lowest) and days to maturity (which was the longest). This depicts that the two varieties RL-294/CML-226 and RML-86/RML-146 have good possibilities for improvement and cultivation in that area.